Analysis Of Ability to Understand Mathematic Concepts of SMP Students During Online Learning on Set Materials - Uswatun Hasanah; Maimunah Maimunah; Yenita Roza (Universitas Negeri Makassar, 2021)
The purpose of this study was to analyze the ability to understand mathematical concepts of junior high school students during online learning on set material. This type of research uses descriptive qualitative. The subjects of this study were grade VII students with a total of 10 students at SMP Negeri 1 Inuman, Kuantan Singingi Regency in the 2021/2022 academic year. The subject selection technique used is purposive sampling technique because the sample cannot be chosen randomly. The data collection technique used in this study was a written test. The questions given are in the form of 5 description test questions that have been prepared based on indicators of mathematical concept ability. The results obtained from this analysis are the ability to understand students' mathematical concepts when online learning is obtained that the ability of students in the high category is 1 student or 10% of the total number of students tested, categorized as sufficient there are 5 students or 50% of all students tested, and in the low category there are 4 students or 40% of the total students tested.